Maori sustainable development in the 21st century: The importance of Maori values, strategic planning and information systems - Harmsworth, Garth; Barclay-Kerr, Kim; Reedy, Tamati (He Puna Korero: Journal of Maori & Pacific Development, 2002)
Keywords: autonomy; economic development; governance; rangatiratanga; self-determination

Maori seeking self-determination or Tino Rangatiratanga? A note - Toki, Valmaine (2017)
Dr Nin Tomas wrote a considered and substantial piece entitled “Indigenous Peoples and the Māori: The Right to Self-Determination in International Law - From Woe to Go” for the New Zealand Law Review published in 2008.² In her conclusion she notes two ways in which self-determination has been implemented by the state: first, by “greater tolerance and benevolence along a series of principled guidelines”,³ and, second, as a “peoples-centred, enabling principle that allows Indigenous peoples to re-establish their social, economic and political institutions”.⁴ In 2010, New Zealand reversed its position and supported the United Nations Declaration on the Rights of Indigenous Peoples (the Declaration).5 With this in mind, this short piece revisits the notion of self-determination by examining the differing dynamics of concepts of external and internal self-determination before a short discussion on pluralism and the relationship between tino rangatiratanga and self-determination. In conclusion some thoughts are offered on a potential form of self-determination that could be consistent with the exercise of tino rangatiratanga.
Keywords: UNDRIP; autonomy; crown; sovereignty; tino rangatiratanga

A Self-Determination Approach to Justifying Indigenous Peoples' Participation in International Law and Policy Making - Charters, Claire (International journal on minority and group rights, 2010)
This paper defends the legitimacy-positive impact of a "contextual-participation approach" to indigenous peoples' participation in international law-making. It argues that indigenous peoples' participation should be substantial where the issue being negotiated at the international level is of considerable interest to indigenous peoples and indigenous peoples have not consented to state representation. The "contextual-participation approach" to indigenous peoples' participation realises the justice in indigenous peoples' claims to remedial efforts to recognise their, mostly lost and historical, sovereignty, and to contemporary and evolving legal, and largely democratic, understandings of self-determination, as expressed, for example, in the UN Declaration on the Rights of Indigenous Peoples. At the same time, it balances indigenous peoples' self-determination entitlements to full participation in international law making, as unjustifiably excluded sovereigns, with contemporary political realities.
Keywords: autonomy; crown law; human rights; indigenous rights; international law; international relations; justice; law; not sure if maori; participation; policy making; political activity; political participation; representation; right wing politics; rights; self-determination; sovereignty; united nations